Can lutein replace annatto in the manufacture of Prato cheese? - Nunes, Natália Moreira; Sobral, Denise; Costa, Renata Golin Bueno; Machado, Gisela Magalhães; Paula, Junio Cesar Jacinto de; Teodoro, Vanessa Aglaê Martins; Pires, Ana Clarissa dos Santos; Pinto, Maximiliano Soares (LWT - Food Science and Technology, 2016)
Prato cheese is a Brazilian yellow-orange cheese traditionally colored with annatto. However, the aim of this study was to replace annatto with lutein, a natural yellow food pigment with potent antioxidant properties. Accordingly, we evaluated the maintenance of antioxidant activity of two concentrations of lutein (16 and 32 mg L−1) in Prato cheese throughout 60 days of ripening, as well as changes in color, pH, texture and ripening profiles, and sensory acceptance of lutein containing Prato cheese. We observed that lutein added to milk was transferred to the curd and antioxidant activity was maintained throughout ripening for both lutein concentrations. The cheese containing the higher concentration of lutein was slightly redder in color than the others; however, the main color changes were due to the ripening. In addition, Prato cheeses containing both lutein concentrations demonstrated similar sensory acceptance compared to cheese containing annatto. Ripening indexes (extension and depth), pH, and texture profile parameters were not affected (p ≥ 0.05) by addition of lutein. Therefore, Prato cheese was found to be a good matrix carrier for lutein, maintaining the antioxidant activity of the colorant. Furthermore, lutein can replace annatto without affecting the properties and acceptance of Prato cheese.
Keywords: Lutein; Prato cheese; Antioxidant activity; Texture; Ripening